2012
DOI: 10.1016/j.diii.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Focal dependent pleural thickening at MDCT: Pleural lesion or functional abnormality?

Abstract: Additional low dose acquisition in prone position should be performed in all patients presenting with focal PT in a dependent and basal location. This may allow to exclude a pleural plaque in case of asbestos exposure but also a pleural metastasis in oncologic patients. These reversible dependent PTs could be related to physiological focal accumulation of lymphatic fluid in subpleural area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Reaching a correct diagnosis of PPs requires a good knowledge of normal locoregional anatomy (transversus thoracic muscle, subcostal muscle, extrapleural fat, etc. ), different features of PPs, and common pitfalls in their diagnosis (focal dependent pleural thickening, pseudoplaques in sarcoidosis and silicosis) [18, 29, 30]. Last but not least, in order to reduce underestimation and to improve current reporting practices of PPs, technical approaches in chest CT execution should also be rigorous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaching a correct diagnosis of PPs requires a good knowledge of normal locoregional anatomy (transversus thoracic muscle, subcostal muscle, extrapleural fat, etc. ), different features of PPs, and common pitfalls in their diagnosis (focal dependent pleural thickening, pseudoplaques in sarcoidosis and silicosis) [18, 29, 30]. Last but not least, in order to reduce underestimation and to improve current reporting practices of PPs, technical approaches in chest CT execution should also be rigorous.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the CTs are performed with the patient in a supine position, the presence of pleural thickening in the dorsal regions, in the absence of PPs in other regions of the pleura, requires an additional acquisition in prone position. This approach will differentiate a real plaque from reversible dependent pleural thickening [29]. According to a recent study by Kim et al [31], an interesting distribution of PPs was found, in particular: diaphragmatic plaques were distributed more commonly on the right side, since the right diaphragmatic dome has a large interface with the lung; mediastinal plaques were distributed more commonly on the left side due to anatomical and mechanical factors such as larger interface with the lung and the pulsating left ventricle pushing the left mediastinal pleura against the adjacent left lung with more mechanical stress than the right mediastinal pleura; chest wall pleural plaques more commonly involved both the basal sides due to combination of high ventilation and gravity in these lung regions.…”
Section: Discussionmentioning
confidence: 99%
“…And there might be false detection of pleural thickening on CT. The thick soft-tissue density at the chest wall–lung interface on the axial CT images sometimes do not truly suggest pleural thickening on CT. Physiological pleural fluid accumulation or dependent atelectasis can mimic the presence of pleural thickening or enhancement on CT [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All examinations were carried out on the same second-generation 320-row scanner ( Aquillion One Vision Edition , Toshiba, Japan). Patients were positioned prone with their arms above their heads [17], so as to avoid gravity dependent parenchymal abnormalities in the posterior regions [18, 19]. Both examinations were acquired with a collimation of 0.5mm*80, a pitch of 0.813 and were reconstructed with Iterative Reconstruction ( AIDR-3D , Toshiba, Japan) set in standard mode.…”
Section: Methodsmentioning
confidence: 99%